A Neuro-educational Study of the Development of the Creativity-based Teaching Program and its Effect. (13th May 2015) - Park, Sun-Hyung; Kim, Kwang-Ki; Lee, Kyung-Hwa
Abstract: This study aims at exploring a possibility of developing a creativity-based teaching program needed for enhancing prospective teachers' creative potentials based on the theories of Sawyer and Renzulli. Neuroimaging tools such as fMRI were used to identify effects of the program on pre-service teachers' neural activations on divergent thinking measured primarily by the Torrance Tests of Creative Thinking (TTCT). Since the research is still in progress, we present a theoretical model for the teaching program, and preliminary test results of comparing changes of neural recruitments in students' brain participated in fMRI with the TTCT.